Paternal Uniparental Isodisomy of Chromosome 11p15.5 within the Pancreas Causes Isolated Hyperinsulinemic Hypoglycemia - Flanagan, Sarah E.; Kapoor, Ritika R.; Smith, Virpi V.; Hussain, Khalid; Ellard, Sian (Frontiers in Endocrinology, 2011)
Background Loss of function mutations in the genes encoding the pancreatic β-cell ATP-sensitive potassium (KATP) channel are identified in approximately 80% of patients with diazoxide-unresponsive hyperinsulinaemic-hypoglycaemia (HH). For a small number of patients HH can occur as part of a multisystem disease such as Beckwith-Wiedemann syndrome (BWS). In approximately 20% of patients, BWS results from chromosome 11 paternal uniparental disomy (UPD), which causes dysregulation of imprinted growth regulation genes at 11p15.5. There is a considerable range in the clinical features and phenotypic severity associated with BWS which is likely to be due to somatic mosaicism. The cause of HH in these patients is not known. Research Design and methods We undertook microsatellite analysis of 12 markers spanning chromosome 11p in two patients with severe HH and diffuse disease requiring a pancreatectomy. In both patients mutations in the KATP channel genes had not been identified. Results We identified segmental paternal UPD in DNA extracted from pancreatic tissue in both patients. UPD was not observed in DNA extracted from the patient’s leukocytes or buccal samples. In both cases the UPD encompassed the differentially methylated region at chromosome 11p15.5. Despite this neither patient had any further features of BWS. Conclusions Paternal UPD of the chromosome 11p15.5 differentially methylated region limited to the pancreatic tissue may represent a novel cause of isolated diazoxide unresponsive HH. Loss of heterozygosity studies should therefore be considered in all patients with severe HH who have undergone pancreatic surgery when KATP channel mutation(s) have not been identified.